Creation and control of valley currents in graphene by few cycle light pulses - Deepika Gill; Sangeeta Sharma; Kay Dewhurst; Sam Shallcross (npj Computational Materials)
Abstract Well established for the visible spectrum gaps of the transition metal dichalcogenide family, valleytronics—the control of valley charge and current by light—is comparatively unexplored for the THz gaps that characterize graphene and topological insulators. Here we show that few cycle pulses of THz light can create and control a >90% valley polarized current in graphene, with lightwave control over the current magnitude and direction. This is underpinned by a light-matter symmetry breaking in the ultrafast limit of circularly polarized light, characterized by a symmetry lowering of the excited state charge distribution. Our findings both highlight the richness of few cycle light pulses in control over quantum matter, and provide a route towards a “THz valleytronics” in meV gapped systems.